Do we recognise the halal logo? / Sitti Aminah Baharuddin ...[et al.] - Baharuddin, Sitti Aminah; Mohd Salleh, Shazwani; Nur Morat, Berlian (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The purpose of this paper is to review the halal certifications approved by JAKIM. There are currently 85 certification bodies recognised by JAKIM. The government should take the responsibility to introduce and promote the different halal logos to the public as to create awareness about the fake and unreliable ones. This is to avoid misunderstandings and doubts, as well as to educate the public about the halal certification logos that have been recognised by JAKIM.